Case report: Successful combination therapy with double-filtration plasmapheresis and rituximab under the condition of the use of a sensor-augmented pump for type B insulin resistance syndrome - Osanami, Arata; Kanda, Masatoshi; Sato, Tatsuya; Akazawa, Chikako; Baba, Shuhei; Komatsu, Hiroaki; Murase, Kazuyuki; Yamashita, Tomohisa; Yano, Toshiyuki (Frontiers in Endocrinology, 2022)
Type B insulin resistance syndrome (TBIR) is a rare disease characterized by refractory diabetes due to severe insulin resistance caused by anti-insulin receptor autoantibodies, and a standard treatment regimen for TBIR has not been established, leading to therapeutic difficulties and high mortality. Since TBIR is known to be associated with autoimmune diseases such as systemic lupus erythematosus (SLE), glucocorticoids are often used as key immunosuppressive agents. However, glucocorticoids have the potential to exacerbate the pathophysiology of TBIR by worsening insulin sensitivity, which leads to hyperglycemia and muscle wasting. Here, we report a case history of a 66-year-old man who was diagnosed as having TBIR in combination with SLE and Sjögren’s syndrome with marked hyperglycemia, ketosis, and muscle wasting. He was successfully treated with combination therapy of double-filtration plasmapheresis (DFPP) and administration of the anti-CD20 monoclonal antibody rituximab without induction of glucocorticoid therapy while using a sensor-augmented insulin pump (SAP) to prevent hypoglycemia. Remission of diabetes was achieved without severe hypoglycemic events and his circulating insulin receptor antibodies became negative after seven months of initiation of these treatments. Based on the successful clinical courses of this case, our report suggests the possibility of an effective therapeutic regimen with DFPP and rituximab under the condition of the use of an SAP for a patient with TBIR without induction of glucocorticoids.